The New Industrial Revolution: Finding life for the buildings left behind - Dawn Bilobran (Acta Polytechnica CTU Proceedings)
From large generating facilities to modest neighbourhood substations, public power structures are an exercise in dichotomy. Captivating yet mysterious, designed with both powerful function and beauty in mind. Quietly playing a role in the development of cities and supporting the activities of home worldwide, the magic of heritage power plants, pumping houses and substations is often hidden behind metal gates and pressed brick facades punctuated with oversized steel windows and carved decorative ornamentations. Efforts to achieve global goals of carbon-neutrality paired with advancements in infrastructure, utility distribution and alternative energies now forces the reconsideration of many unique historic resources. Brimming with astounding potential, power generation facilities present unique challenges that can be deterrents to redevelopment. Adaptive reuse celebrates the contributions of those who designed, constructed and operated the architectural and engineering marvels that powered the world while deterring exceptional building materials from languishing in landfills. As an increasing number of sites are decommissioned how can they be positioned to power new experiences for generations to come? What redevelopment tools are available to incentivize the adaptive reuse of industrial heritage, specifically public utility architecture? How do government-led approaches to adaptive reuse differ?